Ethnopharmacological, chemical, and pharmacological aspects of Halenia elliptica: A comprehensive review - Zhang, Zhifeng; Bian, Qilong; Luo, Pei; Sun, Wenxia (Pharmacognosy Reviews)
Traditional Tibetan medicine (TTM) is an old traditional medical system, which is an effective and natural method of improving physical and mental health, and has been widely spread in the western part of China for centuries. Halenia elliptica (H. elliptica) D. Don, known as “Jiadiranguo” (Tibetan medicine name) is one of the most important herbal medicine in TTM that is from the genus Halenia (family: Gentianaceae). The whole herb can be used as a medicine to treat hepatobiliary diseases and xeransis, and possesses many biological and pharmacological activities including heat clearing, bile benefiting, liver soothing, digestion promoting, blood nursing, detoxification activities, and so on. In modern research, H. elliptica can be used to treat acute or chronic hepatitis, especially hepatitis B. In addition, the chemical compounds of the herb have potent antihepatitis B virus (anti-HBV) activity in vitro. As an important TTM, further studies on H. elliptica can lead to the development of new drugs and therapeutics for various diseases, and more attention should be paid on the aspects of how to utilize it better.
Keywords: Chemistry; ethnopharmacology; Halenia elliptica; pharmacology